«En utstilling om deg, om oss, om måtene vi elsker og mister på»: Museum of Broken Relationships ved Alta Museum - Øien, Maria (Tidsskrift for kulturforskning, 2024)
PS. Some corrections went missing in the last stage of production for this article. These are included in the pdf on this website, but for anyone with the paper edition of the journal, the corrections are on the following pages for your reference: 6, 8, 11 (two corrections), 15 and 17. Museums are increasingly encouraged to bolster their contemporary relevance by becoming more collaborative and active with respect to society. This article describes the genesis of an exhibition titled Museum of Broken Relationships (Brokenships) at Alta Museum, Norway. The exhibition was based on an idiosyncratic concept, which allowed us to both create and investigate museal relevance. This concept was shaped around objects and stories collected from the museum’s audience that symbolise broken relationships. In this article, I show how the Brokenships concept was able to generate relevancy, participation, and inclusion with respect to our local audience in Alta, fulfilling our strategic priority for exhibitions that actively involve the audience. More broadly, the article considers the capacity of an international exhibition concept to articulate local and individual experiences of loss. Engaging with theories about the relevant and affective museum, I show how Brokenships established new and creative points of audience contact that facilitated meaning, dialogue, and inclusivity. In this way, the discussion aims to initiate urgent reflections on what kind of places museums should be and suggest how we can fulfil our societal mission by becoming relevant meeting places. Ultimately, the article gives an idea of how museum exhibitions and dissemination can, in the spirit of Brokenships, bring about changes in a museum’s relationship to its audience.